PERBUATAN MELAWAN HUKUM OLEH NOTARIS TERHADAP PEMALSUAN AKTA OTENTIK DALAM JUAL BELI TANAH DI KABUPATEN REMBANG (STUDI KASUS PUTUSAN NOMOR 05/Pdt.G/2009/PN.Rbg) - Faizal Indra Nor Cahyo; Gunarto Gunarto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2017)
In the sale and purchase of land rights of course there are various parties, including Sellers and Buyers. In this case, Seller (RJ) and Purchaser (IS) 1 purchased land on September 26, 2007 with 10 certificates and total purchase value of land object amounting to Rp 2.232.650.000, - (two billion two hundred thirty two million Six hundred fifty thousand rupiah), due on July 31, 2008, which is until the due date the Purchaser (IS) has not been able to repay it. On the other hand, the Notary of MJ who made the Deed of Sale and Purchase Agreement committed a Law Against Act (PMH) by issuing a Sale and Purchase Deed which should not be issued in case of non-payment. With the formulation of the problem studied are: 1. What are the legal consequences that occur on a Notary who commits an unlawful act against the Deed of Sale and Purchase Land made? 2. How to solve a case against a Notary who committed a Legal Actions (PMH) on the Deed of Sale and Purchase of Land?Approach method used in this research is normative juridical research supported by empirical juridical, research specification is analytical descriptive, writer use primary data and secondary data to get data related to this research.Based on the results of this study, based on the Case Court's Decision Number 05 / Pdt.G / 2009 / PN.Rbg, the case investigation between the Seller (RJ) and the Buyer (IS) on the first issue of the formulation of Notary MJ because it was proven to Act Against Law Falsify the information contained in the Deed of Sale and Purchase which is different from the Deed of Sale and Purchase Bond that has been agreed by both parties, then he must finish the Deed of Sale and Purchase Agreement between the RJ and the IS, and automatically does not Occur And in the formulation of the problem Second, the Buyer (IS) who has made a default booking by not automatically paying the purchase price with the binding agreement between himself and the Seller (RJ), he is charged with a 13th Stipikat to Seller (RJ) discount, With the payment already given To Seller (RJ) by Buyer (IS) is irrevocable and automatically becomes the property of Seller (RJ). As well as Buyer (IS) are charged the court fees that have arisen in advance of the trial.The author's suggestion in this research is for the seller, should be more careful in choosing and revoking the prospective buyer, thus minimizing the undesirable things that will be done by the Buyers so as to disadvantage the Seller, for the buyer, he must have good faith It should always be upheld that there will be no future Seller, for Notary Public, Notary as a public official should have a Neutral attitude toward both parties in the agreement, can be mediator, law-abiding and not doing the Fight Against Act (PMH), by reason No party harmed. Keywords: Sale and Purchase Agreement, Unlawful Actions, Wanprestatie.